Pressure and Isomorphism in Business Education - Valentin Florentin Dumitru; Andrei Stanciu; Madalina Dumitru; Liliana Feleaga (Amfiteatru Economic Journal, 2014)
Aligning the Romanian university education to the Bologna Treaty requirements generated the establishment of the professional skills that have to be obtained by students through business education. To enhance the skills to be acquired by a student along his preparation, the curriculum of the Faculty of Accounting and Management Information Systems within the Bucharest University of Economic Studies was changed several times. This paper follows the evolution of the curriculum for the bachelor's degree of the Faculty of Accounting and Management Information Systems for a period of eight years. To highlight how the curriculum was adjusted according to the expectations of stakeholders the neo-institutional theory was used, applying the concepts of coercive, mimetic and normative isomorphism. The documentation sources were: curriculum for bachelor's degree for the period 2005-2013, syllabuses used during 2011-2013, notes of discussions with representatives of the professional bodies, results of the surveys of students and graduates, interviews etc.
Keywords: A20; 330; professional skills; business education; neo-institutional theory; isomorphism